Mutual Trade of BRICS Countries in the Logic of Integration Cooperation - I. V. Boiko (Евразийская интеграция: экономика, право, политика)
The BRICS is playing an increasingly important role as a new international initiative to counter growing global economic instability. To achieve that mission and to reach the highest form of economic integration — an introduction of a single currency system — the BRICS countries need to start by improving mutual trade relation, which is a prerequisite for creating a common capital and labor markets, which, in turn, is necessary for the formation of a strong economic union. Aim. The aim of the article is to explain a crucial role of improving BRICS mutual trade for further development of economic integration among the member states. The research hypothesis is the following: for strengthening the BRICS integration the member states should change the trade structure in a way of increasing the share of value added commodities in the mutual trade. It will make the complementarity between the countries robust and creates the ground floor for introduction of the own currency and international calculation systems. Tasks. The research tasks comprises analyses of the BRICS’ countries position in the world trade, specifically in merchandise trade, their export potential, the structure of their mutual merchandise trade. Methods. Methodologically the research is based on the theories of convergence and the international division of labour; theories of the “national comparative advantageous”; spatial development of national economy; theories of catching up growth. Statistical, empirical and comparative analyses represent the main methods of the given research. Results. Results of the research are the following: China plays a key role in the production and trade of final manufacturing goods, while the rest of the BRICS countries specialize primarily on the export of raw materials. Moreover, while China’s export is oriented primarily to third country rather than to the BRICS market, the rest of the BRICS countries rely heavily on the import of Chinese goods. The significant gap in the level of economic development of the BRICS countries hinders centripetal interaction between them. Conclusions. In conclusion the author offers a number of recommendations for improving the scale and scope of trade cooperation among BRICS countries. In addition to expanding traditional export it is very important to change its structure towards the production and trade of more technologically complex goods with higher value added. When all BRICS countries move towards achieving this strategic goal, it will deepen their complementarity, and allow less developed member states to catch up with the leading BRICS countries, thereby making this integration more robust and convergent. In this way imports from third countries will be replaced by goods produced and sold on the BRICS market, which can also strengthen mutual trade and economic cooperation between the BRICS countries.